A pilot randomized controlled trial of an early multidisciplinary model to prevent disability following traumatic injury - Browne, Allyson; Appleton, S.; Fong, K.; Wood, F.; Coll, F.; de Munck, S.; Newnham, E.; Schug, S. (2013)
Purpose: Chronic pain, posttraumatic stress disorder (PTSD), and depression are common outcomes following traumatic injury. Yet, screening and early intervention to prevent the onset of these disorders do not occur routinely in acute trauma settings. This pilot study examined the clinical utility of screening and early multidisciplinary intervention for reducing disability following traumatic injury. Method: 142 non-severe head injured trauma inpatients (26% female, Injury Severity Score M = 9.65, M age = 36 years) were assessed for injury-related factors, pain, and psychological function within 4 weeks post injury. Patients were randomly allocated to a Multidisciplinary Intervention (MI) or Usual Care (UC) group. MI patients received assessment and treatment at one and 3 months post injury from pain and rehabilitation medicine doctors, physiotherapists, occupational therapists, and clinical psychologists. Outcomes at 6 months were then compared. Results: Acute pain intensity, posttraumatic adjustment, depression and acute trauma symptoms, and alcohol use predicted a significant 26%, 49%, 56%, and 30% of the variance in pain, depressive, and PTSD severity, and physical mobility respectively at 6 months. Despite MI group patients reporting no improvement in the severity of pain and psychological symptoms, these patients reported significantly improved relief from pain symptoms as a result of treatment at 6 months. Twenty four per cent of the UC group initially below the cut-off for being at risk of developing PTSD/Depression received new clinical diagnoses at 6 months compared with none of the 'not at risk' MI group attendees who remained asymptomatic.Conclusions: Early findings point to the value of early screening to identify patients at risk of treatable pain, physical, and psychological impairments. Moreover, early multidisciplinary intervention models following traumatic injury show promise for protecting against the onset of posttraumatic psychological disorders. Implications for Rehabilitation The prevalence of chronic pain, posttraumatic stress and depressive disorders, and functional disability is high following traumatic injury. Standardized screening within acute trauma settings can identify patients are highest risk of long-term physical and psychological disability. Coordinated early interventions conducted by acute trauma, pain and rehabilitation teams working in collaboration show promise for reducing long-term disability among recently injured trauma patients.